Access is not enough: the impact of emotional costs and self-efficacy on the changes in African-American students' ICT use patterns. Issue 4 (3rd April 2017) - Huang, Kuo-Ting; Cotten, Shelia R.; Rikard, R.V.
ABSTRACT: Previous research has examined the impact of computing interventions to reduce digital inequity. However, few studies focus on factors such as inequalities to material access, Internet use patterns, and affective or emotional anxiety. This paper investigates the potential role of emotional costs and computer self-efficacy in the connection between computer use at home and students' computer use patterns. Data for this research come from pretest and posttest surveys administered to fourth- and fifth-grade African-American students. The results reveal that students' home computer use is a significant predictor of the change in their information and entertainment usage over the course of the intervention. Students' emotional costs partially mediate the relationship between home computer use and information-oriented usage over the intervention period. The findings suggest that providing students access to digital devices is not enough to close the digital divide.